A mild steel shear zone temperature minimization using genetic algorithm and direct search toolbox in cnc turning operation - Minhat, Mohamad; Abd. Rahman, Md Nizam (Praise Worthy Prize, 2013)
The high temperature which occurs in metal cutting operations as a result of heat directly or indirectly influencing the cutting tool and work piece properties. The major part of the energy is converted into heat in primary heat zone which also call shear zone. This paper studies minimization of shear zone temperature during cutting a mild steel work piece by carbide insert cutting tool in computerized numerical control (cnc) turning operation using dry cutting machining. Genetic Algorithm and Direct Search Toolbox methodology is used as optimization method for this purpose. The ideal cutting parameters which help in decreasing the shear zone temperature are obtained. The upper and lower boundaries of cutting parameters will be used as operation constraints. There are many cutting parameters have a huge effect on the shear zone temperature while another have a low.